2005
DOI: 10.1021/bi048080x
|View full text |Cite
|
Sign up to set email alerts
|

An Apolipoprotein E-Derived Peptide Mediates Uptake of Sterically Stabilized Liposomes into Brain Capillary Endothelial Cells

Abstract: A promising strategy to solve the problems of insufficient membrane penetration of drugs and low target specificity is the localization of targeting and uptake-facilitating ligands on the surface of drug-carrier systems. This study investigated the role of a peptide derived from the LDL receptor (LDLr)-binding domain of apolipoprotein E (apoE) in initiating endocytosis in brain capillary endothelial cells. The highly cationic tandem dimer of apoE residues (141-150) was coupled covalently onto poly(ethylene gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 69 publications
(88 reference statements)
3
59
0
1
Order By: Relevance
“…Studies on the apoE receptor-binding region have been reported to narrow its location to the vicinity of amino acid residues 130 to 150 of mature apoE for the binding to LDLRf (20,21). Several synthetic oligopeptides derived from this region mimic certain aspects of receptor binding or apoE function in vitro and in vivo (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the apoE receptor-binding region have been reported to narrow its location to the vicinity of amino acid residues 130 to 150 of mature apoE for the binding to LDLRf (20,21). Several synthetic oligopeptides derived from this region mimic certain aspects of receptor binding or apoE function in vitro and in vivo (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…We have developed a novel Hb-binding peptide to further address this issue: Hb-B10. During peptide synthesis, Hb-B10 was covalently linked to a small fragment of ApoE (hE, residues 141-150) that has been shown to facilitate both the uptake of lipoproteins by small peptides and drug transport by liposomes via endocytic clearance through the ubiquitous heparan sulfate proteoglycan-associated pathway (14,47,51). Although modification of any small peptide might affect function, we found that the pharmacokinetic profile and liver localization of hE-Hb-B10 were very similar to previous reports for other hE-conjugated peptides (17,20,40).…”
Section: Discussionmentioning
confidence: 99%
“…Supported by our results, we present an intriguing paradigm for cancer therapy because this approach can be used for targeting of divergent molecules to cells overexpressing specific surface receptors. Molecules delivered by this approach include antisense oligodeoxynucleotides, ribozymes, and siRNAs, the targeting of which may be used in treatment of different pathologies without adversely affecting healthy tissue (38)(39)(40)(41)(42). There are reports that describe targeting of cytotoxic drugs to tumor cells encapsulated in carriers, including peptide-coated liposomes, as documented in both in vitro and in vivo models (43,44).…”
Section: Discussionmentioning
confidence: 99%